Approaches to cyber weapons classification problem - V. V. Kabernik (Vestnik MGIMO-Universiteta, 2013)
Article focuses on the problem of classification of modern and prospective cyber weapons. Suggested complex of characteristics, based on analytical approach allows for type determination for existing and future cyber weapons. Current wider-known samples are classified and their respective niches are pointed out among different aims for cyber weapons application. Working criteria for differentiation between information warfare and practical cyber warfare is suggested for proper classification of malware, espionage toolkits, hacking tools and combat software.